Peran CSR Memoderasi Hubungan Intensitas Modal, Kepemilikan Institusional, dan Ukuran Perusahaan dengan Penghindaran Pajak - Mega Arisia Dewi; Devi Edriani; Swasta Bangun; Posman WH Hasibuan (Politeknik Ganesha Medan, 2023)
This study is to examine tax avoidance through CSR as a moderating variable: capital intensity, institutional ownership, and firm size. Capital Intensity, Institutional Ownership, and Firm Size are used as independent variables and Tax Avoidance is used as the dependent variable. And CSR as a moderating variable. This research was conducted on manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021. The method of determining the sample in this study was using purposive sampling method so that from 195 populations, a sample of 44 companies was obtained. The research data were analyzed using panel data analysis techniques using Eviews9. The result of the research shows that Capital Intensity has a partial effect on Tax Avoidance, while Institutional Ownership has no partial significant effect on Tax Avoidance and Company Size also has no significant effect on Tax Avoidance. Capital Intensity and Institutional Ownership moderated by CSR have an effect on Tax Avoidance. While Company Size moderated by CSR has no effect on Tax Avoidance. It is hoped that this research can help manufacturers listed on the Indonesia Stock Exchange to find out Tax Avoidance by considering the factors that have a significant effect on tax avoidance such as the effect of capital intensity, institutional ownership and company size as well as CSR as a moderating variable.